Adaptive Response of Peripheral Blood Lymphocytes in Medical Radiation Workers using the Comet Assay: A Preliminary Studyomet Assay: A Preliminary Study - Teja Kisnanto; Darlina Darlina; Arifin Musthafa; Fielda Djuita; Harry Nugroho Eko Surniyantoro; Iin Kurnia Hasan Basri (Indonesian Journal of Cancer, 2022)
Background: Gamma irradiation can cause DNA damage in single and double-strand breaks (SSBs & DSBs), especially in peripheral blood lymphocytes. Radiotherapy medical radiation workers can be exposed to gamma radiation related to their daily work. The comet assay is a sensitive method for analyzing DNA damage, especially SSBs. This study explores DNA damage in medical radiation workers’ peripheral blood lymphocytes as an adaptive response using the comet assay.Methods: Blood samples were obtained from four radiotherapy medical radiation workers as a case study (MRW) and two non-medical radiation workers as controls, and then irradiated with various doses of 0, 1, 1.5, and 2 Gy. Lymphocytes were isolated by histopaque and processed by comet assay on the slide under alkaline conditions. The imaging results were analyzed using the Casplab_1.2.3b2 software. The comet assay parameters observed were Tail Length (TL), % Tail DNA (T.DNA), Tail Moment (TM), and Olive Tail Moment (OTM). The one-way ANOVA method was used to analyze statistically between treatment groups. Results: Based on the study results, an increase in TL, T.DNA, TM, and OTM values in all samples was directly proportional to the increase in radiation dose. However, there was no significant difference (P > 0.05) between the MRW group and the control group on each parameter of the comet assay.Conclusions: From this study, it can be concluded that the level of DNA damage of lymphocyte cells as part of the adaptive response in the MRW and control groups was relatively similar after exposure at doses of 0, 1, 1.5, and 2 Gy.